Development of Mosque Management Information System - TALIB, MUHAMMAD NORMAN HAKIM; MOHAMED, ROZLINI (Applied Information Technology And Computer Science, 2023)
Mosque Management Information system for Felcra Bukit Kepong is a system developed to perform data and information recording work on the Felcra Bukit Kepong Mosque. At the current system, all the recording activities is done manually with handwritten in a book. This method is very subjective and inconsistent because sometimes human make mistake. Based on that situation, a Mosque Management Information system for Felcra Bukit Kepong was developed. This system accepts registration on mosque committee intended to manage their mosque’s information. Through the system, mosque committee can record and store all their data in the system such as a list of mosque committee and event. Besides, congregation also can use the system to get information about the mosque such as duty roster of the mosque committee because the system is a web-based. The prototype model is selected to assist project development of Mosque Management Information system for Felcra Bukit Kepong. Prototype method implements the main phases that present in the system development life cycle methodology, including five phases, which are planning phase, analysis phase, design phase, prototype development phase and the implementation phase.  The development of this system will assist mosque committee to have a better management information system for their mosque.